Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar PAI di SMPI Al-Istiqomah Cipayung-Depok - Resta Rahayu; Amie Primarni; Ismail Mustaqim (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2021)
This study aims to determine the effect of the type of jigsaw cooperative learning model method on learning outcomes of Islamic Education in the material closer to Allah SWT, whose name is very beautiful. The research method used was experimental one group pretest-posttest design and the data used was quantitative data. The subjects of this study were students of class VII A SMPI Al-Iistiqomah. With a total of 30 students consisting of 18 boys and 12 girls. The results of the study were obtained using the Jigsaw type cooperative learning model. The results of data analysis techniques using the t test formula on the pretest and posttest data. The results showed t count 10,6086 > t tabel 2,0484, thus Ho is rejected and Ha is accepted, which means that there is an effect of the cooperative learning model on learning outcomes of Islamic education